Pengembangan Bahan Ajar Perencanaan Pembelajaran Ilmu Pengetahuan Sosial Berbasis Scientific Approach - Wardani Wardani (Mahesa Research Center, 2022)
This study aims to to produce the teaching material planning learning social studies based scientific approach and engetahui student assessment against teaching book learning scientifiec approach planning based social studies. The development of the teaching material learning social studies approach planning based scientific research methods have research and development (R & D). The use of a method of R & D so that yield the product in the form of the teaching material planning learning social studies based scientific approach. A method of R & D that will be used referring to ten steps the theory Borg and Gall. The results of research and discussion on, that teaching materials scientifiec approach planning based on social class obtains a judgment very reasonable from the review the matter, media experts review, and a review of a linguist. In addition, the teaching materials scientifiec approach planning based on social class was tested a small group has given assessments of 9 students were attending a course planning learning social class in the study tadris social class obtains a judgment very reasonable for use. So based on this research writer can conclude that the development planning teaching materials based on social class scientifiec approach should be used.